Use of the CANHEART 'big data' registry to conduct a large randomized registry clinical trial to improve lipid management in Ontario, Canada. (2018) - Khan, Anam; Jia, Jing; Chu, Anna; Udell, Jacob; Farkouh, Michael; Tully, Jack
No abstract available